A Catalytic Approach to Cyclopentenones: Unexpected Challenges in Synthesizing Pent-2,4-dienals - English, Hunter Wade (East Carolina University, 2023)
Transition metal catalysis has long been utilized to facilitate a number of chemical reactions outside the scope of traditional organic chemistry. Because of this, there has been a growing interest in the community in utilizing C-H bonds over C-X bonds as synthetic alternatives with better thermodynamic conditions (lower temperatures, pressures, energies, etc.) and forming C-C bonds. For example, rhodium-catalyzed hydroacylation can be used in the conversion of 4-pentenals to cyclopentanones. The mechanistic foundation of this reaction was applied to the synthesis of chiral 3-substituted indanones, unlocking a whole series of transformations towards the construction of biologically active molecules. The Morehead group recently proposed an alternate synthesis of cyclopentenones via a rhodium-catalyzed intramolecular hydroacylation reaction of penta-2,4-dienals by the following reaction sequence: 1. Vilsmeier-Haack Formylation to form 3-bromo-2-enals, 2. Suzuki Cross-Coupling with vinylboronates, and 3. Hydroacylation. Indeed, all reaction steps were performed successfully starting from acetophenone and allylboronic acid pinacol ester, resulting in 4-methyl-3-phenyl-2-cyclopenten-1-one. However, some surprising results were obtained along the way. It was found that when 3-bromo-3-phenyl-2-propenal underwent Suzuki Cross-Coupling, an unexpected mixture of pent-2,4-dienal isomers was obtained. To investigate this matter, a number of reaction conditions were examined in hopes of finding one with optimal yields and little to no isomerized pent-2,4-dienal product. In addition, a variety of cyclopentenones were synthesized to explore the steric effect in influencing the isomerization process. Some potential mechanistic details of this strange isomerization phenomenon along with results obtained from the synthesis will be reported and discussed.
Keywords: cyclopentenones; hydroacylation; Transition metal catalysts; Organic compounds--Synthesis